Identification of musk compounds as inhibitors of the main SARS-CoV-2 protease by molecular docking and molecular dynamics studies - Belhassan Assia; Salgado Guillermo; Mendoza-Huizar Luis Humberto; Zaki Hanane; Chtita Samir; Lakhlifi Tahar; Bouachrine Mohammed; Gerli Candia Lorena; Cardona Wilson (Journal of the Serbian Chemical Society)
As new drug development is a long process, reuse of bioactives may be the answer to new epidemics; thus, screening existing bioactive compounds against a new SARS-CoV-2 infection is an important task. With this in mind, we have systematically screened potential odorant molecules in the treatment of this infection based on the affinity of the selected odorant compounds on the studied enzyme and the sequence identity of their target proteins (olfactory receptors) to the same enzyme (the main protease of SARS-CoV-2). A total of 12 musk odorant compounds were subjected to a molecular docking and molecular dynamics study to predict their impact against the main protease of SARS-CoV-2. In this study, we have identified two musk-scented compounds (androstenol and vulcanolide) that have good binding energy at the major protease binding site of SARS-CoV-2. However, the RMSD values recorded during dynamic simulation show that vulcanolide exhibits high stability of the protein–ligand complex compared to androstenol. The perspectives of this work are as follows: in vitro, in vivo and clinical trials to verify the computational findings.